The evolution of knowledge-based engineering from a design research perspective: Literature review 2012–2021. (January 2023) - Kügler, Patricia; Dworschak, Fabian; Schleich, Benjamin; Wartzack, Sandro
Abstract: Knowledge-based engineering (KBE) is a research field, which evolved in the 1980s within the context of artificial intelligence (AI), computer aided design (CAD) and computer programming. KBE is often referred to methods, processes and tools for knowledge reuse and design automation promising time and cost benefits in engineering design and originally especially in aerospace and automotive industry. Despite the long period of existence, theoretical foundations of KBE are weak and scientific literature is quite dispersed. About a decade ago, a review by Verhagen et al. collected the state of research and identified future research challenges, which has gained impact within the KBE research community. Therefore, within our review we aim at analysing the evolution of those research challenges in KBE literature during the last decade and further provide an overview of current shortcomings from a design research perspective. The analysis comprises 160 publications from the period of 2012 to 2021. Key findings from the review show, that the challenges from 2012 remain unsolved. We further derived that reuse and adoption of KBE approaches from literature is impeded by (1) a missing conceptualization of KBE research, (2) insufficient links from knowledge source to automation and (3) a tendency of insufficient distinction of the application area.